Effect of mangosteen skin ethanol extract on streptozotocin-induced TNF-α expression - Novera Herdiani; Bambang Wirjatmadi; Kuntoro Kuntoro; Maki Zamzam (AOSIS, 2023)
Introduction: Diabetes Mellitus (DM) is a significant health problem worldwide. DM with poor control of blood glucose levels can eventually cause pancreatic cell disorders, including a decrease in cell mass and function. Mangosteen rind contains xanthone compounds that can be used to protect and reduce cell damage, especially those caused by free radicals. This study aimed to analyze the administration of mangosteen peel ethanol extract on the expression of TNF-α induced by streptozotocin. Materials and Methods: The research was carried out in an experimental laboratory. The research design used was Randomized Post Test Only Control Group Design. The sample is a male rat Wistar strain. Rats were grouped into five groups, namely negative control group, positive control STZ, mangosteen peel extract at a dose of 200 mg/kg BW (K2), a dose of 400 mg/kg BW (K3), an amount of 600 mg/kg BW (K4). Administration of therapy for 14 days orally. Results:  The effects of the mangosteen rind extract had a lower TNF- positive cell count of 3.83 compared to the group that was not treated with the mangosteen rind extract 19.33. All treatment groups showed a significant difference (P0.001) in the number of TNF- protein-expressing cells. This research can inform the public that mangosteen peel's benefits can be developed as prevention and alternative treatment in humans caused by inflammation. Conclusions:  This research affects the administration of ethanol extract of mangosteen peel to decrease the number of TNFpositive cells with an effective dose of 600 mg/kg BW.